Shaping Consumer Purchase Decisions Through Digital Marketing, Product Quality, And Customer Experience - Ardy Jordan; Pande Ketut Ribek; Ni Putu Cempaka Dharmadewi Atmaja (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Consumer purchasing decisions influence how effectively a product or service performs; therefore, they are a crucial component of marketing. When deciding on a product choice, consumers go through a process known as the purchasing decision, which is influenced by various factors, including digital marketing, customer experience, and product quality. The purpose of this study is to identify and explain how Martabak Masbron in Sukawati is influenced by digital marketing, customer experience, and product quality. All customers of martabak products at Martabak Masbron in Sukawati constitute the study population. The study sample consisted of 133 respondents selected using random sampling. Multiple linear regression analysis was used as the analytical method. The results of the study indicate that while digital marketing has a positive but insignificant impact on purchasing decisions at Martabak Masbron in Sukawati, product quality and customer experience have a positive and significant impact. Future studies are advised to include factors such as price and product innovation, service, lifestyle, and packaging, which have a positive and significant impact on purchasing decisions.